2009
DOI: 10.1007/s00227-008-1111-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the high dispersal Atlanto-Mediterreanean sea star Astropecten aranciacus revealed by mitochondrial DNA sequences and microsatellite loci

Abstract: Genetic structure of the high dispersal Atlanto-Mediterreanean sea star Astropecten aranciacus revealed by mitochondrial DNA sequences and microsatellite loci AbstractTo investigate the impact of potential marine barriers on gene-flow in high dispersal marine invertebrates, we assessed the population genetic structure of the sea star Astropecten aranciacus. Samples were obtained from nine locations within the Atlantic and the Mediterranean Sea including populations east of the Siculo-Tunisian Strait. We obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 88 publications
1
48
1
Order By: Relevance
“…The absence of population subdivision at both sides of the Gibraltar Strait strongly contrasts with population differentiation patterns across the AtlantoMediterranean transition described for a number of marine invertebrate species (see Borsa et al 1997;Patarnello et al 2007). Although discrepancies between population genetic patterns for high dispersal echinoderms between Atlantic and Mediterranean sea suggest that similar biological features do not necessarily imply similar population structure (Calderon et al 2008;Muths et al 2009;Zulliger et al 2009), a number of the marine invertebrate species analysed demonstrated either a common pattern of ''genetic divergence'' at both sides of this Strait or isolation by distance (see e.g. Quesada et al 1995;Zane et al 2000;Pérez-Losada et al 2002).…”
Section: Lineage Divergencementioning
confidence: 87%
See 3 more Smart Citations
“…The absence of population subdivision at both sides of the Gibraltar Strait strongly contrasts with population differentiation patterns across the AtlantoMediterranean transition described for a number of marine invertebrate species (see Borsa et al 1997;Patarnello et al 2007). Although discrepancies between population genetic patterns for high dispersal echinoderms between Atlantic and Mediterranean sea suggest that similar biological features do not necessarily imply similar population structure (Calderon et al 2008;Muths et al 2009;Zulliger et al 2009), a number of the marine invertebrate species analysed demonstrated either a common pattern of ''genetic divergence'' at both sides of this Strait or isolation by distance (see e.g. Quesada et al 1995;Zane et al 2000;Pérez-Losada et al 2002).…”
Section: Lineage Divergencementioning
confidence: 87%
“…A bimodal distribution detected for the Mediterranean area emerges from grouping together two genetic pools holding different demographic history. Unimodal distributions in other marine invertebrates have been related to episodes of sea level oscillations during the Pleistocene and prior to the last glacial maximum 18,000 years ago (Zulliger et al 2009;Couceiro et al 2007). According to our results, a rapid population expansion after a glacial period would explain the present diversity of the species (Avise et al 1984).…”
Section: Lineage Divergencementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the differentiation of the sea star Astropecten aranciacus in the Mediterranean Sea is the result of an isolation-by-distance pattern, which allowed for any grouping to be significant. This occurs provided that geographical neighbours are clustered together and without there being a strong discrepancy between samples collected in the northern Adriatic and Aegean sub-basins (Zulliger et al, 2009). Many other examples derive from the population structure of Mediterranean pelagic species, which do not mirror palaeo-oceanographic events to such an extent.…”
Section: The Eastern Mediterranean Mosaicmentioning
confidence: 99%